Developing Sustainability Practices Reporting Measurement Framework For Islamic Banks in Indonesia: A Literature Synthesis - Hanisfy, Ghanef Rayyan; Afgani, Kurnia Fajar (Journal Integration of Management Studies, 2023)
This study aims to develop a theoretical model and measurement framework for reporting sustainability practices in Islamic banks in Indonesia. A survey of 58 selected works of literature was conducted to identify key concepts and insights related to sustainability, social, economic, and environmental dimensions. The theoretical model incorporates these sustainability values and aligns them with Maqasid Al-Sharia, the objectives and principles of Islamic law. By integrating these principles, the model ensures that Islamic banks' sustainability practices in Indonesia are socially, economically, and ethically responsible. The measurement framework facilitates assessing and reporting sustainability practices, enabling Islamic banks to evaluate their social, economic, and environmental impact. This study contributes to sustainable banking by providing a comprehensive model and framework tailored to Islamic banks, promoting transparency, accountability, and responsible finance in Indonesia.